2014
DOI: 10.4315/0362-028x.jfp-13-458
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a Nasogastric Liquid Feed and Shelf-Life Extension Using Gamma Radiation

Abstract: Nasogastric liquid feed formulation (NGLF) was developed for immunocompromised patients who are vulnerable targets of pathogenic assault. NGLF consisted of cereals, pulses, vegetables, and milk powder to provide balanced nutrients; however, the shelf life was only a few hours because this product was highly prone to microbial contamination and proliferation due to its high water content and rich nutrients. Postpreparation storage and distribution was very difficult, even at chilled temperatures. To overcome th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…1A). In a recent study from this laboratory radiation processing (10 kGy) was not found to affect the antimutagenic property of naso-gastric liquid feed prepared for immune-compromised patients (Hajare, Gautam, Nair, & Sharma, 2014). Similar results were obtained for ready-to-eat Kimchi to be used as a space food in Korea where both non-irradiated as well as irradiated (25 kGy) samples showed no mutagenic activity in the bacterial strains of Salmonella typhimurium during Ames test (Song et al, 2009).…”
Section: Honey Displayed Strong Antimutagenicitysupporting
confidence: 63%
“…1A). In a recent study from this laboratory radiation processing (10 kGy) was not found to affect the antimutagenic property of naso-gastric liquid feed prepared for immune-compromised patients (Hajare, Gautam, Nair, & Sharma, 2014). Similar results were obtained for ready-to-eat Kimchi to be used as a space food in Korea where both non-irradiated as well as irradiated (25 kGy) samples showed no mutagenic activity in the bacterial strains of Salmonella typhimurium during Ames test (Song et al, 2009).…”
Section: Honey Displayed Strong Antimutagenicitysupporting
confidence: 63%
“…Gamma irradiation at 10 kGy reduced the microbial load of NGLF to non-detectable levels, and the packed and irradiated product could be stored even up to 1 month at 4 o C without any detectable increase in microbial load. The antimutagenic potential of irradiated NGLF was similar to unprocessed fresh control against ethyl methanesulphonate induced mutagenesis in E. coli cells as evaluated by Rif R assay [76].…”
Section: Specialized Ready To Eat (Rte) Cooked Food Food For Immune-cmentioning
confidence: 90%
“…This assay is advantageous due to its simplicity in deployment, the ability to provide a wide spectrum of forward mutations and low level of spontaneous mutations (approximately 1/10 8 cells) ( Figure 1). It has been extensively used recently to screen the antimutagenic potential of different foods particularly fruits, vegetables and other allied food products at Food Technology Division, Bhabha Atomic Research Centre, Mumbai, India (Figure 2) [20,[50][51][52][53][54][55][75][76][77][78][79]. The assay is better for scoring antimutagenicity over mutagenicity.…”
Section: Rpob-rifampicin Resistance Assaymentioning
confidence: 99%
“…Protein content was determined using Kjeldahl method and fat was quantified by gas chromatography (Agilent Technologies GC-FID, CA, USA) (Hajare, Gautam, Nair, & Sharma, 2014). Carbohydrate content was determined by deducting the percentage values of moisture, ash, protein, and fat from total (100%).…”
Section: Macronutrientsmentioning
confidence: 99%
“…Vitamin A and total vitamin C were also determined as detailed earlier (Hajare et al, 2014). Iron and calcium were determined by atomic absorption spectrometry.…”
Section: Micronutrientsmentioning
confidence: 99%